2018
DOI: 10.3390/w10081053
|View full text |Cite
|
Sign up to set email alerts
|

Reducing High Flows and Sediment Loading through Increased Water Storage in an Agricultural Watershed of the Upper Midwest, USA

Abstract: Climate change, land clearing, and artificial drainage have increased the Minnesota River Basin’s (MRB) stream flows, enhancing erosion of channel banks and bluffs. Accelerated erosion has increased sediment loads and sedimentation rates downstream. High flows could be reduced through increased water storage (e.g., wetlands or detention basins), but quantifying the effectiveness of such a strategy remains a challenge. We used the Soil and Water Assessment Tool (SWAT) to simulate changes in river discharge from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Root‐mean‐square deviation between the observed daily river discharge and both simulation outputs were comparable. Water storage functions implemented in SWAT produced similar peak flow attenuation to MOSM (Mitchell, ; Mitchell et al, ). The water routing model implemented in MOSM runs very quickly and allows the sediment reduction from different water storage scenarios to be immediately evaluated, a key requirement of our decision‐support approach.…”
Section: Mosmmentioning
confidence: 86%
See 1 more Smart Citation
“…Root‐mean‐square deviation between the observed daily river discharge and both simulation outputs were comparable. Water storage functions implemented in SWAT produced similar peak flow attenuation to MOSM (Mitchell, ; Mitchell et al, ). The water routing model implemented in MOSM runs very quickly and allows the sediment reduction from different water storage scenarios to be immediately evaluated, a key requirement of our decision‐support approach.…”
Section: Mosmmentioning
confidence: 86%
“…Level pool routing with a standard spillway discharge relation is used to calculate the outflow hydrograph from each water storage structure (Chow et al, ). Drainage area for water storage locations is estimated using the site topography and flow accumulation values (Mitchell, ; Mitchell et al, ). Cumulative daily water storage in each HYDSB is determined based on the number and size of storage sites.…”
Section: Mosmmentioning
confidence: 99%
“…Many of our research findings have immediate and direct implications on federal and state policies, planning, and restoration strategies. For example, our approach has demonstrated the enormous potential for wetlands to abate nitrogen and sediment transport at watershed scales (Cho et al, ; Hansen et al, ; Mitchell et al, ), with wetland installation shown to be 5 times more effective at reducing nitrate than field‐based approaches (i.e., cover crops) under high to moderate flows (Hansen et al, ). At the same time, stakeholder‐driven modeling of management options to reduce sediment loading enabled consensus agreement among our stakeholder group for hydrology management to be included as an integral part of management portfolios focused on sediment reduction (Cho et al, ).…”
Section: Discussion: Opportunities Enabled By Observatory‐scale Effortsmentioning
confidence: 99%
“…The value of the publicly available hydrology, topography, water quality, imagery, and land cover data sets cannot be overstated and gave the additional data sets here a rich temporal, spatial, and historical context. Many of the data sets were critical in the development of a series of reduced complexity models designed to understand key processes and linkages between processes at the watershed scale (Call et al, ; Cho, ; Cho et al, ; Czuba et al, ; Czuba & Foufoula‐Georgiou, , ; Hansen, Czuba, et al, ), while additional efforts focused on integrating new knowledge into existing mechanistic modeling frameworks like the Soil and Water Assessment Tool (e.g., Kumarasamy & Belmont, ; Mitchell et al, ).…”
Section: Mrb Environmental Observatorymentioning
confidence: 99%
“…Previous studies have largely focused on assessment of BMP performance in reducing nutrient and sediment loss and the subsequent impacts on water quality (Parajuli et al 2013;Weissteiner et al 2013;Kladivko et al 2014;Yeo et al 2014;McLellan et al 2015;King et al 2016;Merriman et al 2018) (see also study reviews in Hashemi et al 2016;Liu et al 2017). BMPs that slow runoff are effective in reducing sediment detachment and transport (Bosch et al 2013;Mitchell et al 2018), although effectiveness can vary depending on watersheds characteristics, BMPs location, and storm magnitude. Gitau et al (2010) argued that water quality improvements may be difficult to observe if they are offset by negative effects of land use changes unrelated to BMPs.…”
Section: Agricultural Practices and Flood Impactsmentioning
confidence: 99%